2012
DOI: 10.5761/atcs.cr.11.01730
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cardiac Perforations Following Radiofrequency Catheter Ablation: Case Report and Literature Reviews

Abstract: Introduction: Multiple cardiac ruptures after radiofrequency catheter ablation that requires surgical repair are uncommon. Methods and Results: We describe a 64-year old male patient with paroxysmal atrial fibrillation who had a cardiac tamponade following radiofrequency ablation. Surgical exploration demonstrated two ruptures in the left atrium, one in the right atrium, and one hematoma in the right atrium. MEDLINE, the Cochrane Library, and related databases were searched up to June 2011 without language res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Nowadays, cardiac radiofrequency ablation is a popular treatment for many kinds of arrhythmias [1], And the method is proved to be feasible and effective especially for symptomatic patients unresponsive to medical treatment [4], even announced as first line therapy for symptomatic supraventricular tachycardia [5]. However it does have some complications, some of which were even potentially life-threatening, for instance, cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, cardiac radiofrequency ablation is a popular treatment for many kinds of arrhythmias [1], And the method is proved to be feasible and effective especially for symptomatic patients unresponsive to medical treatment [4], even announced as first line therapy for symptomatic supraventricular tachycardia [5]. However it does have some complications, some of which were even potentially life-threatening, for instance, cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, some newly-presented complications associated with RFCA were identified, such as pulmonary vein stenosis and atrial-esophageal fistula [6]. Although this sort of major complications are rare and their rate is falling, an article published in 2012 reported that the overall complication rate after RFCA still ranged from 3.9 to 22% and major complications occurred in 3.9% of the patients [4]. Meanwhile the mortality of all patients who underwent RFCA procedures is about 0.1–0.2% [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation